On the potential of linked-basin tidal power plants: An operational and coastal modelling assessment. (August 2020) - Angeloudis, Athanasios; Kramer, Stephan C.; Hawkins, Noah; Piggott, Matthew D.
Abstract: Single-basin tidal range power plants have the advantage of predictable energy outputs, but feature non-generation periods in every tidal cycle. Linked-basin tidal power systems can reduce this variability and consistently generate power. However, as a concept the latter are under-studied with limited information on their performance relative to single-basin designs. In addressing this, we outline the basic principles of linked-basin power plant operation and report results from their numerical simulation. Tidal range energy operational models are applied to gauge their capabilities relative to conventional, single-basin tidal power plants. A coastal ocean model ( Thetis ) is then refined with linked-basin modelling capabilities. Simulations demonstrate that linked-basin systems can reduce non-generation periods at the expense of the extractable energy output relative to conventional tidal lagoons and barrages. As an example, a hypothetical case is considered for a site in the Severn Estuary, UK. The linked-basin system is seen to generate energy 80–100% of the time over a spring-neap cycle, but harnesses at best ≈ 30% of the energy of an equivalent-area single-basin design. Highlights: Differences of single-basin against linked-basin tidal energy systems are presented. Linked-basin systems generate less energy relative to single-basin power plants. Twin-basin systems can be configured to generate power continuously in each cycle.